Social impact as access to advantage: the relevance of the capabilities approach for a theory of philanthropic problem-solving : working paper - Thümler, Ekkehard (Social Science Research Network, 2014)
A core element of contemporary philanthropic practice is the intention to generate meaningful and beneficial social change, usually referred to as 'social impact'. However, it is quite unclear as to what exactly social impact in a demanding sense consists in, and how it comes about. Drawing on empirical research on the social impact of philanthropic foundations in seven European countries, on the one hand, and the capabilities approach as developed by Amartya Sen on the other, the article introduces the mechanism of resource mobilisation as a major explanatory tool for the generation of social impact, and applies central tenets of the capabilities approach to these findings. It concludes that the 'social' element of social impact can be framed as the opening of access to advantage to the target groups of philanthropic actors. Explications of why impact occurs and why it matters in moral terms thus coincide.